Pengaruh Lingkungan Keluarga, Pengetahuan Kewirausahaan, Kepribadian dan Motivasi Terhadap Minat Berwirausaha Dengan Self Efficacy Sebagai Variabel Moderating - Nengrum, Adela Pangestiti Hayu; Mawardi, M. Cholid; Anwar, Siti Aminah (Universitas Islam Malang, 2024)
This research aims to examine the influence of family environment, entrepreneurial knowledge, personality and motivation on interest in entrepreneurship with self-efficacy as a moderating variable in accounting students at Unisma, UMM, UIN Malang. Environment, entrepreneurial knowledge, personality and motivation are considered as independent variables, entrepreneurial interest is the dependent variable, while self-efficacy is a moderating variable. The methodology used in this research is a quantitative approach. Primary data was obtained through distributing questionnaires. The target population is accounting students class of 2020 at Unisma, UMM, UIN Malang, with a sample size determined using the Slovin formula of 85 respondents. The hypothesis was tested using statistical analysis including descriptive statistics, research instrument tests, normality test, classical assumption test, Moderate Regression Analysis (MRA), and hypothesis testing using SPSS Version 29. The test results showed that the family environment did not have a significant effect on interest in entrepreneurship. Entrepreneurial knowledge, personality and motivation have a significant effect on interest in entrepreneurship, self-efficacy does not moderate the influence of the family environment on interest in entrepreneurship. In addition, self-efficacy moderates the influence of entrepreneurial knowledge, personality, and motivation on entrepreneurial interest.Keywords: Family environment, entrepreneurial knowledge, personality, motivation, interest in entrepreneurship, self-efficacy.